Avaliação do potencial antioxidante e antiinflamatório de galactomanana do fungo Tyllopiillus ballllouiii. - Lima, Adriane Trindade Medeiros (2009)
Polymers of mushroom cellular wall are recognized for presenting a lot of biological activities such as anti-inflammatory, antioxidant and anti-tumoral action. Polysaccharides from mushrooms of different molecular mass obtained mushrooms can activate leucocytes, stimulate fagocitic, citotoxic and antimicrobial activity including oxygen reactive species production. In this study were investigated chemical characteristics, in vitro antioxidant activity and anti-inflammatory action in an acute inflammation model of the polysaccharides extracted from Tylopilus ballouii. Results showed that were mainly extracted polysaccharides and that it primarily consisted of mannose and galactose with variable amounts of xylose and fucose. Infrared analysis showed a possible interation between this polysaccharides and proteins. In addition, molecular mass was about 140KDa. Antioxidant activity was tested by superoxide and hydroxyl radical scavenging assay, total antioxidant activity and lipid peroxidation assay. For superoxide and hydroxyl radical generation inhibition, polysaccharides have an IC50 of 2.36 and 0.36 mg/mL, respectively. Lipid peroxidation assay results showed that polysaccharides from Tylopilus ballouii present an IC50 of 3.42 mg/mL. Futhermore, anti-inflammatory assay showed that polysaccharides cause an paw edema decreasing in 32.8, 42 and 56% in 30, 50 and 70 mg/Kg dose, respectively. Thus, these results can indicate a possible use for these polysaccharides from Tylopilus ballouii as an anti-inflammatory and antioxidant.